The Influence of Cooperative Game towards Teamwork of 5th grade Students of Elementary Schools in Surakarta - Cahayani, Arindiar Kusuma; Sudinadji, Muhammad Bagus; Pratisti, Wiwien Dinar (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2019)
Purpose: School-age is a time when children get the basics of knowledge to successfully adjust to adult life and acquire certain skills. This study aimed to see whether there is an influence of cooperative play on the cooperation of 5th-grade students in elementary school.Methodology: The method used was a pre-experimental design with pretest-posttest one group design. The sampling technique used in this study was purposive sampling with criteria of informants determined by the researchers, a total of 300 subjects are 5-th grade students in 8 elementary schools spread in Surakarta. Then for the method of data collection in this study used observation, collaboration scale, and documentation.Results: The results of this study had no effect on cooperative play on the teamwork of 5th-grade elementary school children. However, when viewed from the results of children’s observation data showed behaviors that included the aspect of teamwork when playing cooperation game. Quantitatively, this research was part of proving the influence of quantitative play on teamwork, however, the results of observations indicated behaviors which were consistent with indicators of teamwork.Applications: The teachers might change the variants of cooperative games itself so it would help the students to improve their teamwork